2017
DOI: 10.1002/2016gb005471
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and transport of mercury and methylmercury in peat as a function of changes in water table regime and plant functional groups

Abstract: Climate change is likely to significantly affect the hydrology, ecology, and ecosystem function of peatlands, with potentially important but unclear impacts on mercury mobility within and transport from peatlands. Using a full‐factorial mesocosm approach, we investigated the potential impacts on mercury mobility of water table regime changes (high and low) and vegetation community shifts (sedge‐dominated, Ericaceae‐dominated, or unmanipulated control) in peat monoliths at the PEATcosm mesocosm facility in Houg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Peat mesocosm experiments suggest that changes in hydrological regimes and shifts in vascular plant communities may have a significant impact on Hg cycling in peatlands (Haynes 2017 ). For example, lower, more variable water tables and the removal of Ericaceae shrubs significantly enhanced inorganic Hg and MeHg mobility in peat pore waters and MeHg export from snowmelt, likely from enhanced peat decomposition and internal regeneration of electron acceptors related to water table changes (Haynes et al 2017 ).…”
Section: Anticipated Impacts From Human and Natural Perturbations Inmentioning
confidence: 99%
“…Peat mesocosm experiments suggest that changes in hydrological regimes and shifts in vascular plant communities may have a significant impact on Hg cycling in peatlands (Haynes 2017 ). For example, lower, more variable water tables and the removal of Ericaceae shrubs significantly enhanced inorganic Hg and MeHg mobility in peat pore waters and MeHg export from snowmelt, likely from enhanced peat decomposition and internal regeneration of electron acceptors related to water table changes (Haynes et al 2017 ).…”
Section: Anticipated Impacts From Human and Natural Perturbations Inmentioning
confidence: 99%
“…The two target WT profiles were modeled after typical variability, average-WT years ("high WT") and high variability, low-WT years ("low WT"). The mean difference between the high and low-WT positions was approximately 20 cm throughout the experiment (2012-2014; see Potvin et al, 2015 andHaynes et al, 2017 for hydrograph data). These target WT profiles were maintained by a combination of artificial precipitation additions, translucent rain-exclusion covers, and regulated outflow (spring-only, from~25 cm depth, roughly at the acrotelm-catotelm boundary) from each of the bins.…”
Section: Mesocosm Experimentsmentioning
confidence: 99%
“…However, subsequent study has observed mixed evidence for this hypothesis and has shown higher phenolics with declines in WT position in peat mesocosm experiments controlling for plant functional groups and WT position (Dieleman et al, 2016;Romanowicz et al, 2015). In this same experimental framework, the highest phenolic concentrations were observed in treatments with lowered WT positions and sedge vegetation (Haynes et al, 2017). The accumulation of phenolics can further complicate decomposition dynamics through the occlusion of necessary nutrients, particularly nitrogen (e.g., Northup et al, 1995;Schnitzer, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Though peatlands are widely utilized as palaeoclimatological archives (Benoit et al 1998;Biester et al 2007;Talbot et al 2017), Hg retention in peat is not fully understood. As previously mentioned, Hg can for example be re-emitted to the atmosphere after deposition or transported to downstream ecosystems (Osterwalder et al 2017;Haynes et al 2017Haynes et al , 2019. At a peatland chronosequence near Umeå, Sweden, a study suggested that the mobility of Hg in peatlands was increased with Hg methylation, due to lateral runoff or re-emission (likely the latter) (Wang et al 2020).…”
Section: Introductionmentioning
confidence: 95%